Efficient arsenic removal by a bifunctional heterogeneous catalyst through simultaneous hydrogen peroxide (H2O2) catalytic oxidation and adsorption. (20th November 2021) - Su, Jing; Lyu, Tao; Cooper, Mick; Mortimer, Robert J.G.; Pan, Gang
Abstract: Arsenic (As) is a toxic contaminant in surface waters and groundwater. Oxidation of arsenite (As(III)) to less toxic arsenate (As(V)) by hydrogen peroxide (H2 O2 ) is desirable for enhancing the immobilisation of Arsenic (As). However, this As(III) oxidation process is constrained by the strong pH dependence and the generated As(V) must also be removed for complete As remediation. This study developed and evaluated a novel heterogeneous catalytic system using manganese-doped Lanthanum oxycarbonate (MnL) to catalyse the oxidation of As(III) by H2 O2 and simultaneously adsorb the generated As(V). The presence of MnL enhanced the removal rate of As(III) by 35 times compared with systems utilising H2 O2 alone. Additionally, this superior performance was observed over a wide pH range (5–9), which demonstrated this approach could bypass the well-known pH restriction on oxidation by H2 O2 . Mechanistic studies revealed that the long-lived superoxide radicals (·O2 − /·OOH), present on the particle surfaces and derived from the dissociation of the Lewis acid-base adduct (La–OOH*), were the dominant active species for As(III) oxidation. Mn atoms with low valence states played a crucial role in As(III) oxidation through the provision of extra active sites to facilitate radical production. The La and Mn sites in MnL could rapidly immobilize the generated As(V) by forming precipitates, resulting in a final As removal efficiency of 99% even after three cycles of reutilisation. Overall, this study demonstrates the viability of the proposed novel multi-functional catalyst for efficient As remediation from aqueous environments. Graphical abstract: Image 1 Highlights: Manganese-doped Lanthanum oxycarbonate (MnL) catalysed H2 O2 oxidation to remove As. The approach effectively oxidised As(III) and adsorbed As(V) over a wide pH range. As(III) was mainly oxidised by ROSs generated from La(III) Lewis acid-base adduct. The addition of Mn contributed both to catalytic ROSs generation and As adsorption. MnL exhibited stable performance with coexisting ions and also after 3 times reuse.